Associations Between Parental Attitudes Towards Physical Activity and Physical Literacy Outcomes in Primary School Children: A Cross-Sectional Pilot Study (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Parental attitudes and parenting practices are significantly associated with children’s engagement in physical activity. However, there remains a lack of clear understanding regarding how specific parental priorities are reflected in children’s physical literacy outcomes, particularly within primary school-aged populations. Therefore, the aim of this pilot study was to explore associations between parental attitudes towards sports or active play and physical literacy outcomes in primary school children.Methods: A total of 77 children aged 8–10 years participated in this pilot cross-sectional study. Physical literacy was assessed using the Canadian Assessment of Physical Literacy, second edition, which evaluates four domains: physical competence, daily behaviour, motivation and confidence, and knowledge and understanding. Individual student and family factors, including parental attitudes related to their child’s participation in sports or active play, were assessed using a questionnaire specifically developed by the authors of this study.Results: Pearson correlation analyses indicated positive correlations between parental expectations and children’s overall physical literacy and its components: higher parental expectations for children to learn to play in a team were associated with greater physical competence and overall physical literacy scores (r = 0.273, p < 0.05). Similarly, expectations that the child would improve fundamental movement skills (r = 0.251, p < 0.05), experience success (r = 0.247, p < 0.05), and learn how to follow the rules (r = 0.232, p < 0.05) were all positively correlated with overall physical literacy scores. Children’s Motivation and confidence scores were positively and significantly correlated with parental expectations that the child would learn to play in a team (r = 0.520, p < 0.01) and gain positive experiences through physical activity (r = 0.595, p < 0.01). Negative correlation was identified between parental expectations for enjoyable experience and the children’s Knowledge and understanding scores (r = –0.294, p < 0.01).Conclusion: This pilot study highlights the role of parental expectations in shaping key components of children’s physical literacy, which is essential for sustained engagement in health-enhancing physical activity. The findings suggest that targeting parental expectations, especially those related to social and skill development, may enhance the effectiveness of early intervention programmes